Energy efficiency in energy policy: empirical evidence of direct rebound effect in Portuguese household's demand for electricity - Crujo, Andre Miguel Silva (2015)
This project the direct rebound effect for the electricity demand in Portugal. While we find evidence of such an effect, the estimations also reflect the institutional arrangement that has characterized the electricity market in the country. Also, issues related to energy efficiency promotion are addressed in general putting into context the case study developed.